The Influence of Tax Amnesty Benefit Perception to Taxpayer Compliance - Sari, Ramadhani Indah; Nuswantara, Dian Anita (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2017)
This study aims to examine the effect of tax amnesty benefits perceived on This study aims to examine the effect of tax amnesty on taxpayer compliance on service quality as a moderating variable. The population in this study is the people who follow the tax amnesty in Surabaya is 58,415 individual taxpayers registered in KPP Pratama Surabaya. The sampling technique chosen was judgmental sampling with slovin formula obtained 100 samples. This study was analyzed using partial least square with path analysis model. The results of this study indicate that the benefits of tax amnesty are perceived to affect tax compliance that service quality cannot moderate the relationship between the two. The conclusion in this research is the Taxpayer already feel confident will be abolished taxes that should be owed because they feel watered down and because get tax relief to be more obedient. Good service quality has been done by the Government and fiscal, but with the existence of taxpayer surge that follow the program Amnesty Tax in the last days so that makes Taxpayers feel less comfortable with the services that have been given.